HUBUNGAN TINGGI MUKA AIR DAN DEBIT ALIRAN SUNGAI KARANG MUMUS DI LOKASI DESA PAMPANG KOTA SAMARINDA - Wiadnyana, Dewa Made; Subagiada, Kadek; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2019)
Karang Mumus River Pampang Village Samarinda City has a postal system in accordance with what is needed to overcome or overcome problems related to the environment. This research was carried out around the Pampang River in Samarinda City which was at coordinates 117 ° 06 '44 .00 "BT, 00 ° 27 '36.00" LS - 117 ° 07 '11 .00 "BT, 00 ° 27' 18.00" LS. In this graph measurements are taken to obtain a Rating Curve ( ) and water level (TMA) of 51 data. These values ​​are processed with the help of Microsoft Excel program to get the graphic model. Furthermore, the modeling results are published to get an average value. The results of the study show that the graph in the polynomial shows the best value. Obtained from the results of the modeling of sediment discharge flow that was found one point that was seen to be very increased in data 21.